2017
DOI: 10.1159/000485090
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Functional Iron-Sulfur Domains in ABCE1 Inhibits the Proliferation and Migration of Lung Adenocarcinomas By Regulating the Biogenesis of Beta-Actin In Vitro

Abstract: Background/Aims: ATP-binding cassette transporter E1 (ABCE1), a unique ABC superfamily member that bears two Fe-S clusters, is essential for metastatic progression in lung cancer. Fe-S clusters within ABCE1 are crucial for ribosome dissociation and translation reinitiation; however, whether these clusters promote tumor proliferation and migration is unclear. Methods: The interaction between ABCE1 and β-actin was confirmed using GST pull-down. The lung adenocarcinoma (LUAD) cell line A549 was transduced with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Han et al conducted coimmunoprecipitation to reveal that ABCE1 formed complexes with β‐actin in vivo 142 . Subsequently, Yu et al found that the overexpression of ABCE1 could promote cell proliferation and migration in human lung adenocarcinoma A549 cell models via the interaction of Fe/S domains with β‐actin, while the absence of Fe/S domains in ABCE1 protein could have opposing activity through cytoskeleton rearrangement 143 . Overall, many researchers indicated that Fe/S domains in ABCE1 protein may be a promising therapeutic target for lung adenocarcinomas.…”
Section: Abc Transporter Subfamilies: Structure Function and The Rela...mentioning
confidence: 99%
“…Han et al conducted coimmunoprecipitation to reveal that ABCE1 formed complexes with β‐actin in vivo 142 . Subsequently, Yu et al found that the overexpression of ABCE1 could promote cell proliferation and migration in human lung adenocarcinoma A549 cell models via the interaction of Fe/S domains with β‐actin, while the absence of Fe/S domains in ABCE1 protein could have opposing activity through cytoskeleton rearrangement 143 . Overall, many researchers indicated that Fe/S domains in ABCE1 protein may be a promising therapeutic target for lung adenocarcinomas.…”
Section: Abc Transporter Subfamilies: Structure Function and The Rela...mentioning
confidence: 99%
“…In AC, the expression level of ABCE1 protein were higher than that in the squamous carcinoma. Recently, a series of studies revealed that ABCE1 may be a new interaction protein for β-actin and that the binding of ABCE1 to β-actin requires the Fe-S cluster domain (14,15). These results show that ABCE1 is highly expressed in many malignant tumor cells, indicating that this protein is closely related to the proliferation, invasion and metastasis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%